Estudio geológico y geotécnico en suelos no consolidados, para la instalación de micropilotes, en el túnel de salida de descarga en la Hidroeléctrica de San Gabán III, Carabaya, Puno - Zapata Castillo, Edwar Manuel (2023)
This research work is based on the problem of unconsolidated soils, which occurred in the excavation area of the 60-meter-long Discharge Exit tunnel, this tunnel was considered the most critical of the work due to the type of terrain and because the excavation was carried out below the Interoceanic highway with encampané coverage of approximately 4.20 to 13.70 meters. The procedures that were performed; a numerical modeling to analyze the safety factor, three granulometry laboratory tests, three exploratory boreholes without core recovery and during the excavation according to each advance geomechanical evaluations and monitoring of deformations on the excavation surface, due to lithological and structural factors unfavorable in the work area, the excavation was carried out mechanically in three stages, vault and gables.According to the results of the numerical modeling, laboratory tests and surveys that were carried out, unfavorable lithological and structural factors were identified and due to these factors, umbrella-type micropiles injected with water and cement grout were installed to guarantee the stability of the tunnel before during and after excavation.